Collaborative academic writing in higher education - Cardoso, Adriana (2020)
The didactic experiment is carried out at the Lisbon School of Education, which is part of the network of polytechnic higher education establishments. It belongs to the Lisbon Polytechnic Institute, which comprises seven other higher schools: Institute of Engineering, Accounting and Business School, School of Communication and Media Studies, School of Dance, Theatre and Film School, School of Music, and School of Health Technology. The School of Education offers degrees in Basic Education, Artistic and Cultural Mediation, Visual Arts and Technologies, Community Music (in association with the School of Music), and Sociocultural Community Development. All the graduate curricular programmes offer a curricular unit focused on the development of writing skills. However, it is only the degree in Basic Education that offers a curricular unit entirely dedicated to academic writing (Portuguese Academic Writing, 6 credits), which is allocated to the first year of the curricular plan (1st semester).